Gambaran Status Gizi Balita Berdasarkan Indikator Berat Badan dan Umur di Posyandu Melati Kabupaten Majene 2026 - Sitti Aras Diana; Nur Aisyah (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Introduction: The nutritional status of toddlers is an important indicator for assessing the level of public health because it reflects children’s growth and development. Nutritional problems among toddlers remain a major concern, particularly with regard to the weight-for-age (WFA) indicator, which can reflect overall nutritional status. Monitoring nutritional status through Posyandu serves as a strategic effort in the early detection of nutritional problems in the community. Objective: This study aims to determine the nutritional status of toddlers based on the weight-for-age (WFA) indicator at the Melati Posyandu in Majene Regency, West Sulawesi Province, in 2026. Methods: This is a quantitative study with a descriptive design. The study sample consisted of 63 toddlers selected using total sampling. Data were collected from the Maternal and Child Health (KIA) and Growth Monitoring (KMS) records and analyzed univariately using frequency distributions and percentages to describe the characteristics of the respondents and the nutritional status of the toddlers. Results: The results showed that the majority of toddlers were in the 12–24-month age group (47.6%) and were female (63.5%). Based on nutritional status, most toddlers had a normal nutritional status—45 toddlers (71.4%)—while 18 toddlers (28.6%) were undernourished. Conclusion: The nutritional status of toddlers at the Melati Posyandu in Majene Regency is mostly in the normal category; however, there are still toddlers with poor nutritional status who require further attention and intervention through growth monitoring and improved nutrition education for parents.